Mutualistic ants and parasitoid communities associated with a facultative myrmecophilous lycaenid, Arhopala japonica, and the effects of ant attendance on the avoidance of parasitism. Issue 3 (5th May 2020) - Nakabayashi, Yui; Mochioka, Yukari; Tokuda, Makoto; Ohshima, Issei
Abstract: Herbivorous insects have evolved various defensive strategies to avoid their primary enemies, parasitoids. Many species of Lycaenidae (Lepidoptera) have food‐for‐protection mutualism with ants in their larval stages, where larvae produce nectar for ants and in return ants exclude parasitoids as well as predators. Myrmecophilous relationships are divided into two categories, obligate and facultative, by degrees of myrmecophily. Although parasitoids attacking obligate lycaenids always encounter lycaenid‐specific ant species, parasitoids that use facultative lycaenids are likely to encounter diverse ant species showing various defense systems. However, we know little about the parasitoid community of facultative lycaenid larvae. In this study, we investigated the mutualistic ant and parasitoid communities of a facultative myrmecophilous species, Arhopala japonica, in seven localities in Japan. The present field observation newly recorded four ant species attending A. japonica larvae, and combined with the previous data, the number of attending ant species reached 16, which is nearly the maximum number of reported attending ant species among myrmecophilous lycaenids. However, the present study revealed that almost all parasitized A. japonica larvae were attacked by a single braconid species, Cotesia sp. near inducta . We also assessed the efficiency of facultative ant defense against the parasitoid in the laboratory and revealed that oviposition by Cotesia sp. near inducta females was almost completely hindered when A. japonica larvae were attended by ants. This suggests that the dominant parasitoid does not have effective traits to overcome defensive behavior of ants and that the female wasps oviposit mainly in A. japonica larvae without intensive attendance. Abstract : The present study revealed mutualist and parasitoid communities of a facultative myrmecophilous lycaenid butterfly. Although the lycaenid larvae were attended by at least 16 ant species in total, and this is nearly the maximum number of reported attending ant species among lycaenids, the larvae were almost exclusively parasitized by only one wasp species.